2016
DOI: 10.1016/j.prro.2016.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Radiation therapy for glioblastoma: Executive summary of an American Society for Radiation Oncology Evidence-Based Clinical Practice Guideline

Abstract: Radiation therapy occupies an integral role in treating glioblastoma. Whether and how radiation therapy should be applied depends on characteristics specific to tumor and patient, including age and performance status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
148
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(154 citation statements)
references
References 43 publications
2
148
1
3
Order By: Relevance
“…At this time, given the heterogeneity of patient and treatment characteristics and lack of phase III data, there is insufficient evidence to support one treatment scheme over any other. 111 Given that recurrent GBM often has indistinct borders, a problem compounded by the fact that these lesions typically appear within previously irradiated fields, novel imaging techniques, such as the use of MR-based apparent diffusion coefficient mapping, may prove useful in improving target delineation. 112 …”
Section: Recurrent Gbmmentioning
confidence: 99%
“…At this time, given the heterogeneity of patient and treatment characteristics and lack of phase III data, there is insufficient evidence to support one treatment scheme over any other. 111 Given that recurrent GBM often has indistinct borders, a problem compounded by the fact that these lesions typically appear within previously irradiated fields, novel imaging techniques, such as the use of MR-based apparent diffusion coefficient mapping, may prove useful in improving target delineation. 112 …”
Section: Recurrent Gbmmentioning
confidence: 99%
“…On review of among others recently reported ASTRO [7] and ESTRO-ACROP guidelines for glioblastomas [8], it would appear that substantial innovations with respect to radiotherapy approaches such as target definition, fractionation and planning as well as delivery techniques are largely lacking, or at least these innovations do not appear to find their way to current guidelines. From this unsubstantiated observation, the question arises whether these components of modern radiotherapy have been an integral part of past or current trials performed in glioblastoma patients.…”
Section: Introductionmentioning
confidence: 99%
“…For a newly diagnosed GBM, a maximum safe surgical resection followed by combined radiation therapy and chemotherapy with temozolomide (TMZ) is the current standard of care. Radiation suppresses the growth of GBM and prolongs the survival of patients with GBM, and, therefore, it is central to the treatment of GBM . Radiosensitization by arresting the cell cycle in M‐phase has been shown to increase the efficacy of radiation.…”
Section: Introductionmentioning
confidence: 99%